Prospect . 5. - de Gele Zaal, Gent (Gent : Noordstarfonds vzw, 1987)
Hauters, Werner ; Laerenbergh, Bart ; Opsomer, Geert ; Smitz, Jan ; Storms, Patrick ; Vander Eecken, Dirk ; Vandeweghe, Hans ; Van Gheluwe, Peter
Prospect . 5, De Gele Zaal, Gent, 11.9. - 25.10.1987
boek